Determination of serum creatinine in selected groups of patients by means of HPLC with UV detection – comparison with Jaffé and enzymatic assays - Štramová, Xenie; Kanďár, Roman (University of Pardubice, 2011)
A reversed-phase high-performance liquid chromatography method for the determination of creatinine in human serum samples has been developed. Results from measurements of by a high-performance liquid chromatography on 232 serum samples were compared with enzymatic and Jaffé methods. The serum samples were deproteinized with ethanol. For the separation, a column MAG 1, 250 mm x 4.6 mm, Labiospher PSI 100 C18, 5 :m, was used. The mixture of ethanol and 25 mmol l–1 sodium hydrogenphosphate (3:97 v/v), pH 6.5 was used as a mobile phase. The analytical performance of this method is satisfactory: the intra-assay and inter-assay coefficients of variation were below 6 %. Quantitative recoveries of spiked serum samples were between 101.8 and 106.0 %. The limit of quantification was 10.0 :mol l–1. The results obtained by chromatographic method correlated well with Jaffé assays. Enzymatic method gave at average significantly higher values depending on a group of patients. The presented high-performance liquid chromatographic assay is useful for the analysis of samples where the classical Jaffé or enzymatic methods do not give reliable results and can be a candidate for reference method.